Respuesta :

Piinoy

Answer: -22


Step-by-step explanation:

In the first question, we can simplify 2√8 to 4√2, making it :

(√10 + 4√2)(√10 - 4√2)

When you FOIL, √10(√10) = 10, and 4√2 * -4√2 = -32. The others cancel each other out. So -32 + 10 = -22.



Answer:

1. -22

Step-by-step explanation:

1. There is a special property that we can use. It's a^2-b^2=(a+b)(a-b).

In this case, your a value is sqrt(10) and your b value is 2 sqrt(8).

Thus, (sqrt10 + 2sqrt(8))(sqrt10 - 2sqrt(8)) = sqrt10^2 - 2sqrt(8)^2 = 10 - 32 = -22.